Formulation and Physical Characterization of Chewable Gummy from Galangal Rhizome Extract (Kaempferia galanga L.) as a Nutraceutical Product - Alya Zahira Andarifera; Erizal Zaini; Rahmi Yosmar; Lili Fitriani (Fakultas Farmasi Universitas Andalas, 2025)
The Kaempferia galanga L rizhome (kencur) extract, known in traditional use as an appetite enhancer, was developed into chewable gummy preparations as a nutraceutical product. Due to the taste and odor of extract from natural plants caused less preferable to consume. Therefore the formulation of chewable gummy was addressed to overcome this problem. This study formulated gummy with a concentration of 2% galangal extract and gelatin as gelling agent with concentration variations of 10% (F1), 12.5% (F2), and 15% (F3). The evaluation of the physical properties of galangal rhizome extract chewable gummy included swelling ratio, syneresis, organoleptic, weight diversity, and texture profile analysis (TPA). In addition, a hedonic test was conducted to determine the level of panelist preference. The results revealed that the higher the gelatin concentration, the more significant the changes in the physical properties of gummies. An increase in gelatin plays a crucial role in forming a denser and more stable preparation structure. This impacts the texture regarding chewiness and increase the hardness. The result of TPA showed a significant differences (p<0.05) in the parameters of hardness, gumminess, and chewiness between the three formulations. The results of the hedonic test showed that F3 was the most preferred by the panelists. Based on these results, a gelatin concentration of 15% is recommended for the formulation of chewable gummy galangal rhizome extract.